Faktor-Faktor Determinan Kesuksesan dan Kegagalan Implementasi Sistem Informasi Akuntansi: Tinjauan Literatur - Natalia Caroline; Agus Munandar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the determinants of success and failure in the implementation of Accounting Information Systems (AIS) using a literature review approach. The research method employed is a literature study based on various scientific sources such as journals, books, and previous research related to the topic. The results indicate that the factors influencing the successful implementation of AIS include user competence, user involvement, top management support, system quality, and information quality. Conversely, implementation failure is often caused by technical issues such as poor system quality and non-technical issues such as user resistance, weak communication, and lack of management support. This review emphasizes that the success of AIS implementation depends not only on the technology used but also on organizational readiness, human resource competence, and managerial commitment. The findings of this study are expected to serve as a reference for practitioners and researchers in improving the effectiveness of AIS implementation across organizational sectors.